The Role of Work Motivation as a Mediator on The Influence of Job Stress on Employee Performance - Indar Dwisari; Muhummad Akob Kadir; Hasbiyadi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to determine the influence that job stress has on employee performance, with a focus on the importance of work motivation. The study conducted will explain the relationship between job stress and performance directly and indirectly, namely through motivation as a mediating variable using quantitative methodology. The research population was 126 employees of the Regional Civil Service Agency of South Sulawesi Province. The researcher used a saturated sampling technique, so that the entire population would be sampled. In the process of responding to the hypothesis through a Structural Equation Modeling (SEM) study carried out with the help of Smart PLS version 4 software. The research findings explain that the job stress has an insignificant effect on performance, but has a significant effect on work motivation. Other results prove that there is a significant relationship between work motivation and performance, and work motivation is able to act as a mediator in increasing the influence of job stress on performance to be significant.